Pengembangan Aplikasi Katalog Pembelian Barang Berbasis Web Toko Rizky Plastik - Raynaldo Fadel Muhamad; Paramaresthi Windrayani (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
In today's development where the Internet has become a new place for searching for goods or ordering goods. Where in the past, we still use catalog brochures until now it is easy to find and view goods online. The Rizky Plastics shop itself has been selling plastics since 2000, which sells various plastic items where buyers view and search for items manually. With the times, an online catalog as well as e-commerce is needed to make it easier for buyers or users to find goods, find out information on goods and also order goods easily on all devices such as smartphones or laptops. With the E-Commerce Catalog, it is hoped that it will make it easier for Rizky Plastik Stores to sell and increase the store's brand status on the Internet.